Interrelation between baseline plaque characteristics and changes in coronary atherosclerosis with the PCSK9-inhibitor alirocumab: insights from the PACMAN-AMI randomized trial. (3rd October 2022) - Koskinas, K C; Losdat, S; Shibutani, H; Ueki, Y; Otsuka, T; Haener, J; Fahrni, G; Iglesias, J F; Spirk, D; Van Geuns, R J; Daemen, J; Windecker, S; et al.
Abstract: Background: Patients with acute myocardial infarction (AMI) frequently experience recurrent atherothrombotic events, largely attributable to non-culprit lesions with high-risk characteristics. Statins can halt the progression of coronary atherosclerosis, and addition of protein convertase subtilisin/kexin type 9-inhibitors (PCSK9i) results in incremental low-density lipoprotein cholesterol (LDL-C) lowering and atheroma regression. Purpose: We sought to examine the interrelation between baseline imaging characteristics, on-treatment LDL-C levels, and changes in coronary atherosclerosis as assessed by serial, multi-modality intracoronary imaging in patients with AMI. Methods: This is a post hoc analysis from the PACMAN-AMI randomized trial. Patients were randomly allocated to biweekly alirocumab 150 mg vs. placebo on top of high-intensity statin initiated within 24h of presentation with AMI, and underwent serial imaging of the two non-infarct-related arteries at baseline and after 52 weeks. The primary endpoint was percent atheroma volume (PAV) by intravascular ultrasound (IVUS). Powered secondary endpoints were maximal lipid core burden index (maxLCBI4mm) by near-infrared spectroscopy (NIRS) and minimum fibrous cap thickness (FCTmin) by optical coherence tomography (OCT). Results: Of 300 randomized patients (mean age 58.5±9.8 years, 18.7% women, baseline LDL-C 3.94±0.87 mmol/L), IVUS was serially performed in 265 patients (537 arteries). LDL-C levels decreased to 1.92±0.79 mmol/L with placebo and 0.61±0.61 mmol/L with alirocumab (p<0.001). Compared with placebo (statin alone), alirocumab added to statin resulted in greater PAV reduction (−2.13% vs. −0.92%; p<0.001), greater maxLCBI4mm reduction (−79.42 vs. −37.60; p=0.006), and greater increase in FCTmin (62.67 vs. 33.19 μm; p=0.001). Changes in PAV and maxLCBI4mm were inversely related to on-treatment LDL-C levels, and change in FCTmin was positively related to on-treatment LDL-C levels (Figure 1). Across all patients, we found significant, inverse relationships between change in PAV and baseline PAV [slope: −0.072 (95% CI −0.101 to −0.042); p<0.001], between change in maxLCBI4mm and baseline maxLCBI4mm [slope: −0.437 (95% CI −0.505 to −0.369); p<0.001], and between change in FCTmin and baseline FCTmin [slope: −0.436 (95% CI −0.541 to −0.332); p<0.001]; these findings indicate greater PAV and maxLCBI4mm regression in lesions with greater PAV and LCBI4mm at baseline, and greater fibrous cap thickening in lesions with thinner fibrous caps at baseline. Conclusion: In this study of intensive LDL-C lowering treatment initiated in the acute AMI setting, more favorable plaque changes were observed in patients with lower on-treatment LDL-C levels and in lesions with more adverse baseline plaque characteristics. Whether AMI patients with high-risk plaque features might derive greater clinical benefit from early initiation of intensive LDL-C-lowering therapies requires further investigation. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Sanofi, Regeneron